Preliminary studies of ionospheric behavior during a seismic event of Mw~6.9 at Qinghai station (geog. 33.19° N, 96.75°E) - Aggarwal, Malini; Sharma, D.K.; Bardhan, Ananna (Journal of Indian Geophysical Union, Spl V. 2, p. 127-132, 2016)
The prediction of one of the natural hazards, namely, earthquakes continues to be most challenging for earth scientists. Several recent studies have shown examples from different regions of the world, by which an association noticed between possible electromagnetic precursors and earthquakes has become more authentic. We have investigated the response of ionospheric parameters to the seismic conditions for one of the seismic events of 13 Apr 2010 (Mw~6.9, depth~13.8 km) over Qinghai station (geog. 33.19° N, 96.75°E), using the available online information from the US Geological survey (USGS) website for seismic and space-based GPS-TEC (GPS based total electron content) measurements, for the ionospheric behaviour. The preliminary result shows anomalous depletions in GPS-TE C observed 3-4 days before the seismic event in the ionosphere over nearby stations: Lhasa, Kunming and Urumqi consecutively for ~7-10 hrs.
Keywords: Ionosphere; GPS-TEC; Seismo-Ionospheric coupling